Formulation of children's nutrient-dense recipes from Adansonia digitata pulp and Ocimum gratissimum leaves in North Benin - Bankole, Bissola Malikath; Bodjrenou, Sam; Bodecker, Julia; Noukpoakou, Edwige; Chadare, Flora Josiane; Termote, Celine; Hounkpatin, Waliou Amoussa (Elsevier, 2024)
Neglected and underutilized species (NUS) can play an important role in nutrition and food security. This study aimed to promote the consumption of two NUS, Ocimum gratissimum and Adansonia digitata, by improving recipes that are traditionally consumed by children aged 6–23 months in the Atacora department. Two (02) improved recipes were formulated: baobab pulp-enriched porridge (BPP) and egusi sauce with african basil leaves and red palm oil (ESBR). Formulation was initially carried out using MINITAB 19 mixing software. For each recipe, two factors (two main ingredients of the recipe) were considered for the formulation. The optimized recipes were then tested through a hedonic test with a sample of 66 children in three (03) communes. The nutritional densities of accepted recipes were then determined. Results showed that most of the children liked both recipes formulated. The energy densities of both recipes (1.24 ± 0.03 kcal and 1.89 ± 0.05 kcal/g respectively for BPP and ESBR) met the recommended standards. As for nutritional densities, only iron recommended density was achieved for BPP (4.86 ± 0.12 mg/100 kcal) while for ESBR, in addition to iron density, zinc and vitamin A densities were also achieved. The BPP recipe covered good levels of daily nutritional requirements for one single feed for iron (46.42%) and energy (13.49%) considering the amount consumed by children, whereas the ESBR recipe covered levels of 26.61% for energy, 399.32% for vitamin A, 94.11% for iron and 17.44% for zinc. A better valorization of these species through cooking demonstration sessions addressed to mothers is necessary to ensure the consumption of recipes formulated by communities in general and children in particular.